The effects of developmental trauma on theory of mind and its relationship to psychotic experiences: A behavioural study. (June 2022) - Turner, Ryan; Louie, Krisya; Parvez, Ameerah; Modaffar, Mustapha; Rezaie, Rowan; Greene, Talya; Bisby, James; Fonagy, Peter; Bloomfield, Michael A. P.
Highlights: Developmental trauma exposure was associated with psychotic experiences. Participants with developmental trauma demonstrated significantly lower accuracy on the director task, indicated impaired mentalisation (Theory of Mind) ability. Participants more prone to psychotic experiences demonstrated significantly lower accuracy on the director task, indicated impaired mentalisation (Theory of Mind) ability. Monitoring mentalising ability in early screening may serve as a valuable measures of psychosis risk progression. Interventions targeting mentalisation – such as mentalisation-based therapy - may be helpful for adult survivors of developmental trauma. Abstract: Background: Developmental psychological trauma induces vulnerability to psychosis. However, the mechanisms underlying this association are poorly understood. Impairments in Theory of Mind (ToM) have been observed in adult survivors of developmental trauma and individuals with psychosis. ToM is therefore a candidate mechanism underlying the association between developmental trauma and psychosis. Methods: We used a computerised version of the Director task - where a participant is instructed by a confederate to move an object around a 4 × 4 grid, whilst taking account of whether these objects are visible to a confederate who instructs the participant - to investigate impairments in ToM in 209 participants (age: M  = 37.8, SD=13.6; 56% female). Participants were divided into a) developmental trauma-positive (DT+) and control groups (DT-) based on their history of developmental trauma and b) then further into subclinical (S) and healthy groups (H) as based on psychotic experiences indexed by the CAPE-P15. After exclusion, the numbers in each group were: DT+ H (47), DT+ S (84), DT-H (54), DT-S (12). (Total: 197). Results: Developmental trauma exposure was associated with psychotic experiences (OR: 7.89, p < .001), which remained significant after controlling for demographic and clinical confounds (adjusted R 2  = 0.452, R 2 change = 0.0184, p  = .009). Participants with developmental trauma (F1, 194 ) = 5.46, p  = .020, ηp 2  = 0.027) and participants more prone to psychotic experiences (F1, 194 ) = 4.71, p  = .031, ηp 2  = 0.024) demonstrated significantly lower accuracy on the Director task relative to their respective control, after controlling for the effects of age. Conclusions: ToM deficits are associated with self-reported developmental trauma and psychotic experiences. Further work is needed to explore these relationships further and whether they represent generalised or specific effect effects on developmental trauma and psychopathological domains.